Omega-3 polyunsaturated fatty acid supplementation for improving peripheral nerve health: protocol for a systematic review. Issue 3 (25th March 2018) - Zhang, Alexis Ceecee; MacIsaac, Richard J; Roberts, Leslie; Kamel, Jordan; Craig, Jennifer P; Busija, Lucy; Downie, Laura E
Abstract : Introduction: Damage to peripheral nerves occurs in a variety of health conditions. Preserving nerve integrity, to prevent progressive nerve damage, remains a clinical challenge. Omega-3 polyunsaturated fatty acids (PUFAs) are implicated in the development and maintenance of healthy nerves and may be beneficial for promoting peripheral nerve health. The aim of this systematic review is to assess the effects of oral omega-3 PUFA supplementation on peripheral nerve integrity, including both subjective and objective measures of peripheral nerve structure and/or function. Methods and analysis: A systematic review of randomised controlled trials that have evaluated the effects of omega-3 PUFA supplementation on peripheral nerve assessments will be conducted. Comprehensive electronic database searches will be performed in Ovid MEDLINE, Embase, the Cochrane Central Register of Controlled Trials (CENTRAL), US National Institutes of Health Clinical Trials Registry and the WHO International Clinical Trials Registry Platform. The title, abstract and keywords of identified articles will be assessed for eligibility by two reviewers. Full-text articles will be obtained for all studies judged as eligible or potentially eligible; these studies will be independently assessed by two reviewers to determine eligibility. Disagreements will be resolved by consensus. Risk of bias assessment will be performed using the Cochrane Collaboration risk of bias tool to appraise the quality of included studies. If clinically meaningful, and there are a sufficient number of eligible studies, a meta-analysis will be conducted and a summary of findings table will be provided. Ethics and dissemination: This is a systematic review that will involve the analysis of previously published data, and therefore ethics approval is not required. A manuscript reporting the results of this systematic review will be published in a peer-reviewed journal and may also be presented at relevant scientific conferences. PROSPERO registration number: CRD42018086297 .